Building a Rock-Solid Slide: Management Consulting, PowerPoint, and the Craft of Signification. (August 2016) - Bourgoin, Alaric; Muniesa, Fabian
The diagrammatic slideshow constitutes a crucial communicational instrument in management consulting. However, its semiotic implications remain poorly understood. How do consultants create slides that they deem significant? How do they recognize a good slide or an effective diagram? What practical criteria do they use? To tackle these questions, we develop a pragmatist approach based on the theory of signs of Charles S. Peirce. Drawing from data collected through ethnographic participant observation, our study analyzes how a team of consultants drafts a single slide intended to represent the problems of a client organization and assesses the evolving strength of the document. We identify three recurrent conditions of robustness—impact, accuracy, and layout—and discuss them in the light of Peirce's distinction of iconic, indexical, and symbolic capacities in signification.